1995
DOI: 10.1177/096032719501400404
|View full text |Cite
|
Sign up to set email alerts
|

Changes in connective tissue macromolecular components of Yucatan mini-pig skin following application of sulphur mustard vapour

Abstract: 1 The aim of this study was to determine the nature of the macromolecular alterations in Yucatan mini-pig skin which occur following application of sulphur mustard vapour, with particular reference to laminin and type IV collagen. 2 The immunostaining of transfer blots from skin extracts run on SDS-PAGE gels revealed no evidence of cross-link ing of type IV collagen or laminin. Laminin was, however, found to be partially degraded as determined by the reso lution of 132 and 143 kDa fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 26 publications
0
10
2
Order By: Relevance
“…Only laminin appeared to be degraded almost completely following exposure of skin to Lewisite, as indicated by the much reduced level of laminin antigen staining on the blots, although a small amount of laminin antigen was resolved between 45 and 66 kDa. This contrasts markedly with Lindsay and Rice (1995) in a study of the effects of sulphur mustard exposure in Yucatan mini-pigs, in which case sulphur mustard only induced a partial cleavage of laminin and had no effect on type IV collagen integrity.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…Only laminin appeared to be degraded almost completely following exposure of skin to Lewisite, as indicated by the much reduced level of laminin antigen staining on the blots, although a small amount of laminin antigen was resolved between 45 and 66 kDa. This contrasts markedly with Lindsay and Rice (1995) in a study of the effects of sulphur mustard exposure in Yucatan mini-pigs, in which case sulphur mustard only induced a partial cleavage of laminin and had no effect on type IV collagen integrity.…”
Section: Discussioncontrasting
confidence: 84%
“…The fact that damage was found to both of these critically important basement membrane components, and to laminin in particular, following percutaneous Lewisite exposure of large white pigs strongly suggests that the potency of this vesicant may be attributable to its effects on these essential macromolecules that mediate dermo-epidermal attachment processes. The effects of Lewisite on laminin and type IV collagen observed in the present study are more severe than those found in a previous study on sulphur mustard effects in pigs (Lindsay and Rice, 1995), suggesting that there are important differences in the mechanism of action of both vesicants. That Lewisite should produce more severe effects on basement membrane macromolecules and yet generate more rapid healing of skin burns than sulphur mustard may be attributable to alkylation (by sulphur mustard) of the DNA and RNA of skin cell types, their metabolic processes and connective tissue components (Rice and Brown 1999;Naghii, 2002) that would normally be involved in skin regeneration and healing responses.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…To date a number of proteins have been shown to aggregate or breakdown on SM exposure, e.g. various keratins [7][8][9], and laminin [10,11]. There has been little research looking at the direct interaction of SM with cell membrane-associated proteins.…”
Section: Introductionmentioning
confidence: 99%